Analytical validation of a proliferation-based molecular signature used as a prognostic marker in early stage lung adenocarcinoma. (September 2015) - Warf, M Bryan; Fosso, Placede G; Hughes, Elisha; Perry, Michael; Brown, Krystal L; Reid, Julia E; Kolquist, Kathryn A; Wagner, Susanne; Gutin, Alexander; Roa, Benjamin
Aims: The aim of these studies was to validate the analytical performance of a cell cycle progression (CCP) gene signature that provides prognostic information for early stage lung adenocarcinomas.Materials & methods: Formalin-fixed paraffin-embedded (FFPE) lung resections were evaluated by quantitative RT-PCR for the expression of 31 target and 15 housekeeper genes comprising the CCP score.Results: The signature had a standard deviation (SD) of 0.06 score units and a dynamic range spanning CCP scores between -13 and 14. The average amplicon efficiencies for target and housekeeper genes were 107% and 105%, respectively. All but one amplicon had a SD <0.5 CT .Conclusion: These studies demonstrate that the gene signature is robust and reproducible, making it suitable for use in a clinical setting.